The Effect of Graphene Oxides Sheets on the Mechanical Properties of Graphene Fibres (Journal of Fiber Bioengineering and Informatics, 2018)
Graphene Oxides (GOs) of different sheet size were prepared by a novel modified Hummers' method. The heating time of expandable graphite, and oxidizing time of expanded graphite are demonstrated in order to have an influence on GO sheet size. Over-heated graphite in the microwave causes the decrease of GO sheet size, leading to a reduction in the performance of graphene fibres' mechanical properties. The oxidation mechanism was proposed by analyzing the chemical structure model of GO and evaluating its functional groups. Aggregation of GO sheets leads to the increase of internal shear stress, thus changing the viscosity of GO dispersion. Viscosity is another characteristic relating to the forming of graphene oxide liquid crystals (GO LC) and its phase transformation, which affects the mechanical properties of graphene fibres in the process of wet-spinning.